2023
DOI: 10.1002/oa.3201
|View full text |Cite
|
Sign up to set email alerts
|

Fishhooks, fishing spears, and weaving: The bone technology of Madjedbebe, Northern Australia

Abstract: Archeological assemblages of osseous material culture are rare in the Australian context, especially in the north where environmental conditions are not usually conducive to organic preservation. Nevertheless, more than 230 bone artifacts were recovered from the site of Madjedbebe, located in the Mirarr clan estate of the Alligator Rivers region of the Northern Territory. Of these artifacts, 199 have been identified to tool type. Here, we present the analysis of this exceptional assemblage, including the recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…However, considering that osseous barbed points are known to be used as projectiles, it is likely that more of the fractures documented resulted from impact damage; either direct (tip) or recursive (base). Additionally, the fractures visible at the proximal end of the barbed points are consistent with wear from fixed hafting [ 54 ].…”
Section: Resultsmentioning
confidence: 97%
“…However, considering that osseous barbed points are known to be used as projectiles, it is likely that more of the fractures documented resulted from impact damage; either direct (tip) or recursive (base). Additionally, the fractures visible at the proximal end of the barbed points are consistent with wear from fixed hafting [ 54 ].…”
Section: Resultsmentioning
confidence: 97%
“…These most recent studies revealed a stone assemblage including late Pleistocene-aged grindstones, ground edge axes and ground ochres (Clarkson et al 2017). Subsequent detailed studies have included the analyses of the mid-Holocene shell midden layer (Woo 2020), magnetic susceptibility of the sediments (Lowe 2014), burial patterns (Lowe et al 2014), the archaeobotanics (Carah 2017;Florin et al 2022), Holocene-aged ochres (Cox 2013;Crough-Heaton 2021), flaked stone artefacts (McNeil 2016), ground stone assemblage (Hayes 2015) and bone points (Basiaco 2018;Langley et al 2023).…”
Section: The Madjedbebe Site Contextmentioning
confidence: 99%
“…Following debate (e.g., Bowdler 2017; Clarkson et al 2018; Smith et al 2020; Veth 2017; Williams et al 2021; Wood 2017), public discourse in Australia has strongly adopted the findings from Madjedbebe, and the 65,000-year date is now routinely cited as the basis for the world's “longest continuous culture” in parliamentary documents, policy documents, government statements, and across the media. A multitude of specialist studies were forthcoming from this project—although, under current arrangements, researchers now seek direct approval from GAC to work on materials excavated from Madjedbebe (e.g., Crough-Heaton 2021; Langley 2021; Langley et al 2023; Litster 2022; and see the case study below), rather than obtaining access via the lead researcher, as was formerly the case (Basiaco 2018; Carah 2017; Cox 2013; Florin 2013, 2020; Florin et al 2020, 2021; Hayes 2015; Hayes et al 2021, 2022; Lowe 2014; Marwick et al 2017; McNeil 2016; Moody 2016; Woo 2020).…”
Section: Gac Community Leadershipmentioning
confidence: 99%